DEX‐Induced SREBF1 Promotes BMSCs Differentiation into Adipocytes to Attract and Protect Residual T‐Cell Acute Lymphoblastic Leukemia Cells After Chemotherapy - Ruinan Jia; Tao Sun; Xin Zhao; Guosheng Li; Yuan Xia; Ying Zhou; Wěi Li; Wei Li; Daoxin Ma; Jingjing Ye; Min Ji; Chunyan Ji (Advanced Science, 2023)
Abstract T‐cell acute lymphoblastic leukemia (T‐ALL) is an aggressive malignant blood disorder with a high rate of relapse. Patients relapse as a result of minimal residual disease (MRD), which originates from residual T‐ALL cells in the bone marrow microenvironment (BMM). In the present study, it is observed that adipocytes increase dramatically in the BMM of T‐ALL patients after exposure to chemotherapeutic drugs. Then, it is proved that adipocytes attract T‐ALL cells by releasing CXCL13 and support leukemia cell survival by activating the Notch1 signaling pathway via DLL1 and Notch1 binding. Furthermore, it is verified that dexamethasone (DEX) induces adipogenic differentiation by enhancing the expression of SREBF1 in bone marrow mesenchymal stromal cells (BMSCs), and an SREBF1 inhibitor significantly decreases the adipogenic potential of BMSCs and the subsequent ability of adipocytes to support T‐ALL cells in vitro and in vivo. These findings confirm that the differentiation of BMSCs to adipocytes induced by DEX contributes to MRD in T‐ALL and provides an auxiliary clinical treatment to reduce the recurrence rate.